PERSEPSI GURU SEKOLAH DASAR NEGERI 192 PEKANBARU TERHADAP KURIKULUM MERDEKA - Wiliya; Zariul Antosa; Erlisnawati (STKIP Subang, 2026)
Merdeka Curriculum (Kurikulum Merdeka) is a new curriculum launched by the Indonesian Ministry of Education, Culture, Research, and Technology in 2022 as an enhancement to the 2013 Curriculum, which grants greater flexibility to teachers and schools in designing learning experiences tailored to students' needs. The success of its implementation largely depends on teachers' perceptions as the primary practitioners in the classroom. Teachers' perceptions of this new curriculum are a determining factor in its successful implementation; however, no specific study on this matter at SD Negeri 192 Pekanbaru has previously been conducted. Therefore, this study aims to identify and describe the perceptions of teachers at SD Negeri 192 Pekanbaru toward the Merdeka Curriculum.This study employed a descriptive qualitative approach, with data collected through in-depth interviews, non-participatory observation, and documentation study. The research subjects consisted of six classroom teachers who have implemented the Merdeka Curriculum at SDN 192 Pekanbaru. Data analysis followed the interactive analysis model by Miles and Huberman, encompassing the stages of data collection, data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation techniques.The findings reveal that the teachers at SDN 192 Pekanbaru hold a positive-adaptive perception toward the Merdeka Curriculum. First, teachers demonstrate a reasonably good understanding of the core concepts of the Merdeka Curriculum, such as Learning Outcomes (Capaian Pembelajaran/CP), Learning Objectives (Tujuan Pembelajaran/TP), and the Learning Objective Pathway (Alur Tujuan Pembelajaran/ATP), although variation among teachers remains. Second, teachers' perceptions of learning planning are positive; however, a gap exists between conceptual understanding and actual implementation in the preparation of instructional materials. Third, teachers have made efforts to apply student-centered learning models, although the use of IT-based media and differentiated instruction has not been uniformly implemented. Fourth, teachers understand and apply formative assessment, yet the development of Higher-Order Thinking Skills (HOTS)-based instruments still requires improvement. Fifth, perceptions toward the Pancasila Student Profile (Profil Pelajar Pancasila/P5) are the most positive and consistent, with all teachers integrating P5 values into the learning process.